(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Email systems are critical to modern communication but are increasingly targeted by cyberattacks due to the sensitive information they handle. This comprehensive guide explores the various types of attacks on email systems, including phishing, spear phishing, whaling, business email compromise (BEC), email spoofing, malware delivery, and spamming. It also delves into more sophisticated techniques like man-in-the-middle (MitM) attacks, credential harvesting, ransomware, impersonation attacks, denial of service (DoS) attacks, and email account compromise. By examining the methods and impacts of these attacks, this guide aims to enhance awareness and preparedness against potential threats. Furthermore, it outlines preventive measures, such as using strong passwords, enabling two-factor authentication (2FA), implementing email filtering, educating users, employing encryption, updating software, and monitoring email activity. Through understanding and mitigating these threats, individuals and organizations can better protect their email systems and sensitive information from cybercriminal activities.